Um framework extensível para interoperabilidade dinâmica entre componentes distribuídos - Nascimento, Sidney Cassemiro do (2013)
The popularization of middleware occurred in recent years promoted the emergence of different technological models. Because of this diversity, interoperability between different models of software components becomes essential to promote the integration of heterogeneous parts. The heterogeneity of middleware is a challenge for the development of distributed systems. The problems involved with interoperability are treated in general by adopting middleware systems able to mediate and establish communication between different platforms. In this context, this dissertation proposes then a standard framework for interoperability between different models of software components. To decrease the coupling of the proposed platform, was implemented a distributed framework with a extensible architecture to support new component models and new types of binding as independent plugins. The proposed framework enables the reuse of heterogeneous components (i.e. OpenCOM and Fractal) in the composition of complex distributed systems, as well as interoperability between distributed components of such models. To confirm the benefits in performance, usability and extension, this dissertation presents a case study of a distributed application based on Comanche Web Server using composition of heterogeneous components to assess the feasibility of the proposed framework.